A Compendium of Italian Economists at Oxbridge Contributions to the Evolution of Economic Thinking - Baranzini, Mauro; Mirante, Amalia (Springer International Publishing : Imprint: Palgrave Macmillan, 2016)
This study examines five decades of Italian economists who studied or researched at the Universities of Oxford and Cambridge between the years 1950 and 2000. Providing a detailed list of Italian economists associated with Hicks, Harrod, Bacharach, Flemming, Mirrlees, Sen and other distinguished dons, the authors examine eleven research lines, including the Sraffa and the neo-Ricardian school, the post-Keynesian school and the Stone's and Goodwin's schools. Baranzini and Mirante trace the influence of the schools in terms of 1) their fundamental role in the evolution of economic thought; 2) their promotion of four key controversies (on the measurement of technical progress, on capital theory, on income distribution and on the inter-generational transmission of wealth); 3) the counter-flow of Oxbridge scholars to academia in Italy, and 4) the invigoration of a third generation of Italian economists researching or teaching at Oxbridge today. A must-read for all those interested in the way Italian and British research has shaped the study and teaching of economics.